Polar lipid profiling of olive oils as a useful tool in helping to decipher their unique fingerprint. (December 2016) - Alves, Eliana; Melo, Tânia; Rey, Felisa; Moreira, Ana S.P.; Domingues, Pedro; Domingues, Maria Rosário
Abstract: Olive oil (OO), a key ingredient of the Mediterranean diet, is frequently subjected to adulteration. A lipidomic approach has been used to study the lipid composition of Portuguese commercial OOs, to find out differences in their profile or a unique fingerprint, namely in the polar lipid pool. Extra virgin (EVOO, n  = 3) and virgin olive oils (VOO, n  = 3) were analysed. The fatty acids (FA) were analysed by GC-MS and the triacylglycerols by MALDI-TOF-MS. The polar lipid fraction was obtained through solid phase extraction and analysed by hydrophilic interaction liquid chromatography-electrospray ionization-MS. The amount of FA C16:0 and C18:1 was significantly different between the EVOOs and the VOOs. Both categories of OO were discriminated by the FAs C18:3, C18:2 and C16:1 . Five classes of phospholipids were identified in the polar lipid fraction, with significant differences in phosphatidylcholines. Besides FA, it is important to study the polar lipidome to identify minor components that could help to reveal a fingerprint associated with each OO. Highlights: Major and minor lipid components were studied in extra virgin and virgin olive oils. Lipidomics was used to analyse the fatty acids, triacylglycerols and polar lipids. Multivariate statistic analysis of the fatty acid profile discriminated olive oils. Significant differences on the polar lipid profile of olive oils were observed. Glycolipids and a betaine lipid are reported in olive oil for the first time.